Estimation of Shear Wave Velocity of Darul Imarah District, Aceh Besar, Indonesia by Using 1D HVSR Inversion. Issue 1 (May 2020) - Yusran, Y; Khalqillah, Aulia; Muksin, Umar; Syukri, Muhammad; Rizal, Syamsul; Ismail, Nazli
Abstract: A total of 19 locations of Horizontal to Vertical Spectral Ratio (HVSR) measurements was conducted in Darul Imarah District, Aceh Besar, Indonesia. The objective of the research is to investigate the shear wave velocity ( V s ) structure. This survey is important to analyze a structural characteristic through a V s, considering the measurement points intersect to Aceh Segment Fault. One of the methods to obtain Vs is 1D HVSR inversion. In this paper, we analyzed only four of 19 measurement points of HVSR data to estimate Vs, they are AB03, AB08, AB09 and AB19 points. The inversion results show that the four points have four layers with different Vs . The average of Vs 30 of AB03, AB08, AB09 and AB19 were calculated, they are 150.90 m/s, 197.16 m/s, 150.45 m/s and 316.80 m/s, respectively. The AB09 has the lowest average of Vs 30 (highest amplification) than the other points and has soft soil composition. Furthermore, based on the average of Vs 30 and amplification, the subsurface of AB03, AB08 and AB19 may have combination soft soil and stiff soil in 30 m depth. The complete analysis of average of Vs 30 structure will be conducted at all sites including a 3D velocity structure will be derived from the interpolation of 1D velocity.